Supramolecular Surface Charge Regulation in Ionic Covalent Organic Nanosheets: Reversible Exfoliation and Controlled Bacterial Growth - Mal, Arindam; Vijayakumar, Samiyappan; Mishra, Rakesh K.; Jacob, Jubi; Pillai, Renjith S.; Dileep Kumar, B. S.; Ajayaghosh, Ayyappanpillai (Angewandte Chemie International Edition, 2020)
Poor control on the exfoliation of covalent organic frameworks (COFs) remains a disadvantage for their application as two‐dimensional nanosheets. An equally important problem is the reversible control at the available surface charges on COFs. Herein, a strategy for the reversible exfoliation, re‐stacking, and surface‐charge control of a propidium iodide based ionic covalent organic framework, PI‐TFP, using cucurbit[7]uril (CB[7]) induced molecular recognition, is reported. The surface charge on PI‐TFP facilitates its initial self‐exfoliation. However, complexation with CB[7] resulted in re‐stacking with concomitant decrease in zeta potential from +28±3.0 to +0.004±0.003 mV. Addition of 1‐adamantylamine hydrochloride (AD) facilitates decomplexation of PI‐TFP from CB[7], resulting in exfoliation and an increase in zeta potential to +24±3.0 mV. Such control on the exfoliation, re‐stacking, and the associated regulation of the surface charge in PI‐TFP was exploited for controlling bacterial growth. Thus, the activity of E. coli and S. aureus bacteria obtained with the self‐exfoliated PI‐TFP could be reversibly controlled by the CB[7]/AD pair. The reversible exfoliation, re‐stacking, and surface charge control of a propidium iodide based ionic covalent organic framework (iCOF) is achieved by using cucurbit[7]uril (CB[7]) induced molecular recognition. The reversible surface charge control is exploited for supramolecular regulation of on‐demand bacterial growth on the iCOF.